2007
DOI: 10.1080/02841850701308378
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanism of cognitive control impairment in patients with hepatic cirrhosis: a functional magnetic resonance imaging study

Abstract: This study demonstrates that patients with hepatic cirrhostic have cognitive control deficiency. The abnormal brain network of the ACC-PFC-parietal lobe-TFG is the neural basis of cognitive control impairment in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 29 publications
5
52
0
Order By: Relevance
“…This study demonstrated an early impaired and compensatory neural mechanism during visual judgment already in the earliest stages of HE. Zhang et al 14 used a Chinese character Stroop task as the target stimulus to investigate the neural mechanism of cognitive control impairment in patients with cirrhosis by using the fMRI method, providing further evidence in support of the fact that patients with cirrhosis have impaired cognitive control function and that the abnormal anterior cingulate cortexprefrontal cortex-parietal ''fusiform" cortex circuit could be the neural mechanism responsible for this impaired cognitive control (Fig 6). However, paradigms should be kept simple to isolate specific brain areas in the task-induced fMRI.…”
Section: 6mentioning
confidence: 99%
See 2 more Smart Citations
“…This study demonstrated an early impaired and compensatory neural mechanism during visual judgment already in the earliest stages of HE. Zhang et al 14 used a Chinese character Stroop task as the target stimulus to investigate the neural mechanism of cognitive control impairment in patients with cirrhosis by using the fMRI method, providing further evidence in support of the fact that patients with cirrhosis have impaired cognitive control function and that the abnormal anterior cingulate cortexprefrontal cortex-parietal ''fusiform" cortex circuit could be the neural mechanism responsible for this impaired cognitive control (Fig 6). However, paradigms should be kept simple to isolate specific brain areas in the task-induced fMRI.…”
Section: 6mentioning
confidence: 99%
“…36 Many behavioral studies have claimed the existence of neuropsychological abnormalities, such as attention and fine-motor alterations, in patients with cirrhosis without overt HE. 13,14 Thus, it is rational and feasible to investigate brain function changes in patients with cirrhosis.…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation
“…Zafiris and colleagues demonstrated that MHE is associated with impaired coupling between visual judgment areas (70). A study conducted by Zhang and colleagues compared brain fMRI data in 14 patients with cirrhosis and 14 healthy volunteers (71). An incongruous word reading task and incongruous color-naming task (testing for attention and interference) highlighted various cerebral areas on fMRI: there was greater activation of the bilateral parietal and prefrontal cortices in the patients with cirrhosis (72).…”
Section: Functional Mrimentioning
confidence: 99%
“…Abnormal suppression occurs in epilepsy, 10 attention deficit hyperactivity disorder, 11 Alzheimer disease, 12 and traumatic brain injury. 13 Studies in patients with cirrhosis have demonstrated functional connectivity between regions including the anterior and posterior cingulate cortices, parietal lobe, and fusiform gyrus, 14 and abnormal deactivation of the posterior cingulate, precuneus, and ventral medial prefrontal cortices. 15 DMN activation and altered neural functioning during MHE treatment are not known.…”
mentioning
confidence: 99%